Eighteenth-century transplantations : new literary lives, forms and contexts - Paluchowska-Messing, Anna; Lipski, Jakub; Maciulewicz, Joanna (New York, NY : Routledge, 2025)
"This collection foregrounds the identity of eighteenth-century British literature as enmeshed within a dynamic intercultural traffic, participating in importing and exporting literary and cultural forms. Eighteenth-Century Transplantations places the existence of this transcultural circulation at the centre of attention and presents its products in a unique configuration, whereby literary transplants into the British context, out of it, and their transmedial afterlives are set together in order to showcase these processes of. The concept of transplantation, borrowed from and evocative of eighteenth-century's first horticultural experiments, is offered here as a useful kinetic model to conceptualize a range of practices involved in relocating a literary text into a new cultural environment"--
Keywords: English literature -- 18th century -- History and criticism; Cultural fusion in literature; LITERARY CRITICISM / Books & Reading; SOCIAL SCIENCE / Popular Culture